Application of radiofrequency ablation for the treatment of intermediate‐stage hepatocellular carcinoma. Issue 3 (March 2017) - Nouso, Kazuhiro; Kariyama, Kazuya; Nakamura, Shinichiro; Oonishi, Ayano; Wakuta, Akiko; Oyama, Atsushi; Ako, Soichiro; Dohi, Chihiro; Wada, Nozomu; Morimoto, Yuki; Takeuchi, Yasuto; Kuwaki, Kenji; et al.
Abstract: Background and Aim: Transcatheter arterial chemoembolization (TACE) is a standard therapy for the treatment of intermediate‐stage hepatocellular carcinoma (HCC). In this study, we tried to elucidate the possibility of using radiofrequency ablation (RFA) as an alternative treatment of intermediate‐stage HCC. Methods: Among 246 patients who were initially diagnosed with intermediate‐stage HCC, 76 who were treated with TACE (TACE group) and 91 who were treated with RFA (RFA group) were enrolled in this study. The risk for survival was analyzed with the Cox Proportional Hazard Model, and the survival rates were compared using propensity score matching. Results: About half (50.6%) of the intermediate‐stage HCC patients in the RFA group were diagnosed with Barcelona Clinic Liver Cancer substage‐B1 (BCLC‐B1) compared with only 19.7% of the patients in the TACE group. Survival of the RFA group was longer than that of TACE group in patients with BCLC‐B1 and BCLC‐B2. In contrast, no difference between groups was observed in patients with BCLC‐B3/4. Multivariate analysis revealed that large tumor size (>30 mm, hazard ratio = 1.685, P = 0.043), high des‐γ‐carboxyprothrombin (>100 mAU/mL, hazard ratio = 1.920, P = 0.012), and TACE group (hazard ratio = 1.896, P = 0.016) were significant risk factors for survival. Overall 3‐year survival of the patients in the RFA group (69.5%) was significantly longer than that of patients in the TACE group (51.5%) after propensity score matching ( P = 0.032). No significant adverse events were observed in either group. Conclusions: RFA was useful for the treatment of less advanced intermediate‐stage HCC and could be an alternative to TACE in selected cases.